An effective strategy for preparing nickel nanoparticles encapsulated in polymer matrix-derived carbon shell with high catalytic activity and long-term durability toward urea electro-oxidation. (28th April 2021) - Luong, Quang Thien; Kang, Sun Young; Lee, Dohyeon; Song, Jihyeok; Karuppannan, Mohanraju; Cho, Yong-Hun; Kwon, Oh Joong
Abstract : A promising route has been employed to prepare nickel nanoparticles encapsulated by carbon shell with enhanced catalytic activity and durability for electro-oxidation of urea. Abstract : Direct urea fuel cells have been recognised as a potential approach for sustainable development. However, the low catalytic activity of urea oxidation has hindered its practical application. Herein, by employing a facile pyrolysis strategy, we successfully synthesised nano-sized nickel particles encapsulated in a carbon shell supported on carbon nanofibers. The morphology and structure of the synthesised catalysts were characterised by TGA, XRD, FE-SEM, HR-TEM, and XPS. The catalytic activity of the catalysts toward the electro-oxidation of urea was investigated using cyclic voltammetry. Ni@2CS/CNF was found to possess the smallest size and uniform particle distribution on the carbon support, thus manifesting exceptional performance and remarkable long-term durability. Therefore, this study demonstrated that the nickel-encapsulated by carbon shell can be applied for urea oxidation as an efficient catalyst in direct urea fuel cells.